Inferior mesenteric artery lymph node metastasis in rectal cancer treated with neoadjuvant chemoradiotherapy: Incidence, prediction and prognostic impact. Issue 1 (January 2017) - Sun, Y.; Chi, P.; Lin, H.; Lu, X.; Huang, Y.; Xu, Z.; Huang, S.; Wang, X.
Abstract: Aim: To assess the effect of neoadjuvant chemoradiotherapy (nCRT) on inferior mesenteric artery (IMA) nodal metastasis and identify predictors for IMA nodal metastasis in locally advanced rectal cancer (LARC) after nCRT. Method: Propensity score matching of 1167 patients with LARC was performed. Clinicopathological predictors and survival rates were analyzed using univariate and multivariate analyses. Results: Compared to surgery alone, nCRT reduced the incidence of IMA nodal metastasis (before matching, 4.8% vs 9.1%, p = 0.004; after matching, 4.3% vs 10.1%, p = 0.002). Logistic regression analysis revealed that poorly differentiated (OR = 5.955, p < 0.001), tumors located above the peritoneal reflection (OR = 3.513, p = 0.005), and preoperative CEA levels ≧10 ng/ml (OR = 4.774, p = 0.005) were associated with IMA nodal metastasis. Time intervals to surgery ≧6 weeks were associated with fewer IMA nodal metastasis (OR = 0.274, p = 0.009).Over a median 40-month follow-up, the 3-year overall survival and disease-free survival rates were 63.0% and 43.1% in IMA-positive patients, respectively, which were significantly lower than the corresponding 89.0% and 82.4% rates in IMA-negative patients. Cox regression analysis revealed that IMA nodal metastasis was independently associated with unfavorable 3-year DFS. Conclusion: nCRT reduced the incidence of IMA node metastasis. Tumors located above the peritoneal reflection, poorly differentiated, and higher preoperative CEA levels were associated with IMA nodal metastasis after nCRT. IMA lymph node dissection is beneficial to certain patients with IMA nodal metastases, and the oncologic benefit may be improved if IMA nodal metastasis can be predicted.